Analysis On the Implementation of Income Tax Article 21 Incentives Policy for Taxpayers Affected by The Covid-19 Pandemic - Andrian Sukmana; Haula Rosdiana (Universitas Muhammadiyah Gorontalo, 2021)
In response to the crisis caused by Covid- 2019 outbreak, the government issued the Minister of Finance Regulation Number 23/PMK.03/2020 regarding tax incentives for taxpayers affected by the coronavirus outbreak as part of the national economic recovery program, which along with the pandemic situation has been amended or replaced several times. One of the incentives provided is the Income Tax Article 21 incentive. Thisresearchexaminesto gives a comprehensive review and analysis of the implementation of the Income Tax Article 21 incentive for taxpayers affected by the Covid-19 Pandemic and the problems encountered throughout the policy's implementation. This study uses a descriptive qualitative approach to explain objectively, in detail, and in-depth the results obtained. Observation, in-depth interviews, and documentation techniques were used in collecting the data. This study indicates that although the Income Tax Article 21 incentive is beneficial for the recipients in spending during the pandemic, its implementation faces various challenges. In terms of the realization of this incentive, it is relatively low compared to the initial budget allocation, so it is doubtful that it will provide the expected multiplier effect on economic growth, as the objective of this policy. Thus, the improvement in economic and public consumption growth cannot be linked directly to the contribution of the Income Tax Article 21 incentives policy alone because many other things and policies can affect the economy.